2013
DOI: 10.1007/s40266-013-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in the Elderly

Abstract: Atrial fibrillation (AF) is the most common arrhythmia in older adults with a prevalence of 9 % in adults aged 80 years or older. AF patients have a five times greater risk of developing stroke than the general population. Using anticoagulants for stroke prevention in the elderly becomes a challenge because both stroke and bleeding complications increase with age. CHA₂DS₂-VASc and HAS-BLED scores are currently used as stroke and bleeding risk evaluations. When the HAS-BLED score is 3 or higher, caution and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 78 publications
1
22
0
3
Order By: Relevance
“…While not solely a disease of the elderly, the risk of all types of heart disease, including atrial fibrillation (AF) increases with age (39). AF is the most common arrhythmia in older adults, with a prevalence of 9% in adults aged 80 yr or older (40). Similar trends for AF to increase with age have also been documented before in mice (24 compared with 2 mo) (35).…”
Section: Discussionsupporting
confidence: 72%
“…While not solely a disease of the elderly, the risk of all types of heart disease, including atrial fibrillation (AF) increases with age (39). AF is the most common arrhythmia in older adults, with a prevalence of 9% in adults aged 80 yr or older (40). Similar trends for AF to increase with age have also been documented before in mice (24 compared with 2 mo) (35).…”
Section: Discussionsupporting
confidence: 72%
“…Anticoagulant medications can reduce stroke risk by 60-70% [20]. Scoring systems, such as CHADS2 and, more recently, CHA2DS2-VASc, can be used to calculate stroke risk CHA2DS2-VASc places extra weight on advanced age and is useful in further identifying the truly low stroke risk patient [21,22]. With a CHADS2 score of zero or one before initiation of anticoagulation, recompute with the CHA2DS2-VASc scale.…”
Section: Stroke and Anticoagulationmentioning
confidence: 99%
“…With a CHA2DS2-VASc of zero, patients do not require anticoagulation. With a score of one, anticoagulation with warfarin or NOACs should be undertaken [22]. Just over half of elderly patients who are at very high risk for stroke are anticoagulated.…”
Section: Stroke and Anticoagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the HAS-BLED score, when it is ≥3 caution and efforts to correct reversible risk factors are advised, oral anticoagulants are recomended in all CHADS 2 scores of ≥2, with a Ia recomendation 1A [19]. However, it has been shown that estimates of bleeding risks by treating physicians are overstated, by as much as 18% [20] and as such under-usage is frequent.…”
Section: Introductionmentioning
confidence: 99%